Breast cancer progression when definitive surgery is delayed. Issue 4 (27th January 2021) - Alaidy, Ziad; Mohamed, Ahmed; Euhus, David
Abstract: Deferment of definitive surgery for some breast cancers has been proposed as a way to conserve hospital resources during the COVID‐19 pandemic. However, it is currently unknown which, if any, breast cancers are capable of progressing during a few to several months of observation. The difference between clinical size at diagnosis and final pathology size was assessed in 315 stage I–III primary invasive breast cancer patients who were divided into three groups based on the time between diagnosis and definitive surgery. Size differences over time were used to estimate specific growth rates. Compared with the group with ≤60 days between diagnosis and surgery, tumor growth was observed for 12% of tumors in the 61‐ to 120‐day group and 17% of tumors in the >120‐day group ( p for trend = 0.032). Significantly greater specific growth rates were observed for tumors >2 cm by pathology measurement and for pathology node‐positive patients ( p  < 0.0001 and p  = 0.006, respectively). Specific growth rates were significantly greater for luminal B breast cancers than for luminal A breast cancers ( p  = 0.029) but not for triple‐negative or HER2‐positive breast cancers not selected for neo‐adjuvant chemotherapy. There was no evidence of nodal progression with surgery delay. Fewer than 20% of stage I‐III breast cancers not selected for neo‐adjuvant chemotherapy evidence size progression during follow‐up periods ranging from 61 to 294 days. Clinical‐pathological features cannot reliably predict which tumors will grow. Luminal B phenotype was the only clinical variable known at the time of diagnosis that strongly predicted growth. If resource limitations mandate prioritization schemes for breast cancer surgery, luminal B breast cancer may be the highest priority.